Effect of thread pitch and frictional coefficient on the stress concentration in metric nut-bolt connections - DRAGONI, Eugenio (1994)
By means of the finite element method, this paper establishes how much the stress state within standard metric nut-bolt connections is affected by variations of the thread pitch and of the frictional coefficient. Following a validated simplified approach, the actual three-dimensional geometry of each connection is replaced by an axisymmetric model which recreates the outline of the joint on an appropriate meridional section. The numerical data prove that, for prescribed nominal thread diameter and bolt load, The peak stress in the screw monotonically increases as the pitch decreases. Further, as far as complete sticking between nut and bolt is not achieved, the stress level linearly increases with the coefficient of friction, the rate of variations being higher at the lowest pitches.